2012
DOI: 10.1155/2012/829743
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation of WAIS Digit Span with Clox 1 and the Dementia Rating Scale in MCI

Abstract: Individuals with MCI declined in performance over 6 months in the Clock-drawing (Clox 1) and the WAIS Digit Span tests, but not in the Dementia Rating Scale (DRS). Individual performance on Clox 1 and Digit Span did not correlate after 6 months. Performance on the Digit Span Test also did not correlate with the DRS, but performance on Clox 1 correlated with the DRS. Performance in Clox 1 was, therefore, not a predictor of performance in the Digit Span Test. These findings support the use of a test battery cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…For instance, working memory performance has predictive value in MCI patients with respect to conversion to dementia. 18 - 19 Although the present findings showed that deficits are present in verbal and visuospatial memory, not all currently available working memory tests reveal impairments. A promising approach may lie in novel working memory paradigms that rely on the episodic buffer.…”
Section: Discussioncontrasting
confidence: 62%
“…For instance, working memory performance has predictive value in MCI patients with respect to conversion to dementia. 18 - 19 Although the present findings showed that deficits are present in verbal and visuospatial memory, not all currently available working memory tests reveal impairments. A promising approach may lie in novel working memory paradigms that rely on the episodic buffer.…”
Section: Discussioncontrasting
confidence: 62%
“…From a clinical perspective, working memory assessment is important. For example, working memory performance has predictive value in patients with MCI with respect to the development of dementia [38,39]. Although episodic deficits during disease progression have been widely investigated and are the benchmark of a probable diagnosis of AD, more recent research has investigated working memory and executive function decline during MCI, also referred to as the preclinical stage of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent case reports have also provided anecdotal evidence associating chronic N 2 O use with subacute combined degeneration and limb weakness [12], myeloneuropathy [13], pernicious anemia [14], hematologic changes and risk of thrombosis [15,16], myocardial infarction [17], pneumomediastinum [18], vitamin B12 deficiency with lower motor neuronal degeneration [19,20], and stroke [21], and many conditions that are considered significant risk factors for AD onset, including headache [22], anemia [23], gait imbalance/ataxia [24], thrombosis [25], stroke [26], and myocardial infarction [27]. Moreover, clinical evidence suggests that trace N 2 O exposure induces impairments in the Digit Span Test [28], a test that has predictive power in identifying cognitive decline in participants with mild cognitive impairment (MCI)—a condition often prodromal to AD [29].…”
Section: Environmental Nitrous Oxide (N2o) Exposure and Ad Pathologymentioning
confidence: 99%